Spectra of Generalized Bochner–Riesz Means on Weighted Spaces. (27th July 2019) - Fang, Qiquan; Tao, Xiangxing
Abstract: In this paper, we introduce a family of generalized Bochner–Riesz means and show that their spectra on weighted L p spaces, 1 ≤ p < ∞, are either the whole complex plane or the interval [ 0, a ] for some a ≥ 0 . Also we extend the above spectral property to weighted Triebel–Lizorkin spaces, weighted Besov spaces, and weighted Herz spaces.